DEVELOPMENT OF PHYSICS E-LEARNING BASED ON PROBLEM BASED LEARNING TO IMPROVE STUDENTS' HIGH-LEVEL THINKING ABILITIES AND LEARNING INTERESTS IN FLUID MATERIALS - Yoli Wilanda Fitri; Fakhruddin Fakhruddin; M Rahmad (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
One of method increase ability think level tall that is with application of suitable learning media For competence 21st century one of them is e-learning. E-learning in research This developed with the PBL learning model which consists of above five syntax with objective capable increase HOTS skills and interests Study students . Based on results analysis needs carried out by researchers obtained that 91.5% of students interested For learning with using e-learning. Research This aiming For describe development e-learning physics based on problem based learning , acquiring e-learning physics that is feasible and practical For used in learning physics . Physics e-learning validated by 3 validators using sheet evaluation validity , as well as tested practicality by 3 teachers and 20 participants educate use sheet evaluation practicality . Research results show that e-learning physics based on problem based learning declared very worthy by the validator with mark validation 3.49 for material , 3.51 for media and 3.52 for pedagogy . Besides That based on practicality test results obtained the average value of teacher practicality is 88.00 (very practical) and the average practicality is 88.00 (very practical). student 89.50 (very practical).